ClusterE-ZSL: A Novel Cluster-Based Embedding for Enhanced Zero-Shot Learning in Contrastive Pre-Training Cross-Modal Retrieval - Umair Tariq; Zonghai Hu; Khawaja Tauseef Tasneem; Md Belal Bin Heyat; Muhammad Shahid Iqbal; Kamran Aziz (IEEE Access)
Zero-shot learning (ZSL) in a multi-model environment presents significant challenges and opportunities for improving cross-modal retrieval and object detection in unseen data. This study introduced a novel embedding approach of vector space clustering to address image-to-text and text-to-image retrieval problems effectively. We proposed an iterative training strategy; unlike the CLIP model, which directly compares visual and textual modalities, our model concatenates by clustering trained image and text features in common vector space. We use cross-modal contrastive and multi-stage contrast loss to improve the unsupervised learning of our model. This integration makes it possible to achieve proper clustering on embedding, which enhances the image-text matching problem in zero-shot learning tasks. We rigorously evaluate our model performance on standard benchmark datasets, including Flickr30K, Flickr8K, and MSCOCO 5K, achieving notable improvements with accuracies of 91.3%, 88.8%, and 90.3%, respectively. The results demonstrate the better performance of our model over existing methods but also show its effectiveness in enhancing cross-modal retrieval in zero-shot learning.